Avenues for Youth Representation in Uganda - Kagambirwe, Gerald; Muriaas, Ragnhild L. (CMI, 2023)
Youth representation has emerged as an important political issue worldwide. In sub-Saharan Africa, Uganda can be considered as a pioneer in catering for the presence of youth in political decision-making bodies. Yet, while increased youth representation in democratic contexts is encouraged and applauded, policies aimed at youth inclusion in autocratic regimes can be criticized as serving the purpose of co-optation and control. Through a combination of a historical review of formal political structures and qualitative interviews of youth leaders in Uganda, this working paper aims to take a bottom-up approach to understand the purpose of youth engagement in political structures considered as a tool for government control. The analysis reveals that even if young politicians clearly understand the weakness of the organizations and how they are manipulated by the structures, they also explain how this flawed system of representation provides several opportunities—both for mobilizing against and in favour of the current regime. The rather complex system of youth representation must thus be seen in the light of historical developments. No rulers, even autocratic ones, can know all the consequences of their actions, and decisions can be spontaneous reactions to events and immediate needs, not necessarily well-developed strategies.
Keywords: Avenues; Youth